The Role of Regional Governments in Developing Draft of Regional Regulations - Galuh Sekar Widjayanti; Arpangi Arpangi; Amin Purnawan (Universitas Islam Sultan Agung, 2022)
This study aims to understand the role of local governments in the preparation of the Ranperda, especially the Ranperda concerning Regional Public Water Supply Companies in the Jepara Regency area. In addition, it is also viewed from the perspective of Islamic law on the steps taken by the local government. This study uses an analytical-descriptive type of research, and uses a juridical-sociological approach. In accordance with the type and approach used, the types and sources of data are Primary Data and Secondary Data, with data collection methods used through interviews with related informants and literature studies in the form of statutory regulations and related literature books. The results of this study are that the role of local governments in the preparation of regional regulations is in accordance with the regional government laws, namely; has the right to submit Draft Regional Regulations, including in this case the Submission of Ranperda concerning Regional Public Drinking Water Companies in the Jepara Regency area.